VD_FINDINFO Arrêt / 2022 / 733 vom 6. September 2022 - VD Tribunal cantonal (2022)
RÉVISIONDÉCISION, COMPENSATION DE CRÉANCES, RECOUVREMENT, PRESCRIPTION | 53 LPGA, 61 let. i LPGA, 101 LPA-VD, 102 LPA-VD